Immunomodulatory extracellular vesicles: an alternative to cell therapy for COVID-19. (2nd December 2021) - Gupta, Ashim; Shivaji, Kashte; Kadam, Sachin; Gupta, Manu; Rodriguez, Hugo C.; Potty, Anish G.; El-Amin, Saadiq F.; Maffulli, Nicola
ABSTRACT: Introduction : SARS-CoV-2 induces a cytokine storm and can cause inflammation, fibrosis and apoptosis in the lungs, leading to acute respiratory distress syndrome (ARDS). ARDS is the leading cause of mortality and morbidity the associated to COVID-19, and the cytokine storm is a prominent etiological factor. Mesenchymal stem cell-derived extracellular vesicles are an alternative therapy for the management of inflammatory and autoimmune conditions due to their immunosuppressive properties. The immunomodulatory and tissue regeneration capabilities of extracellular vesicles may support their application as a prospective therapy for COVID-19. Areas Covered : We explored the clinical evidence on extracellular vesicles as antiviral agents and in mitigating ARDS, and their therapeutic potential in COVID-19. Expert Opinion : Clinical trials using extracellular vesicles are registered against COVID-19 associated complications, with some evidence of safety and efficacy. Extracellular vesicles present an alternative potential for cell therapy for COVID-19 management, but further preclinical and clinical investigations are needed.